Obstacles to Investigating Sexual Harassment Cases at the Indramayu Police Station - Noerul Putri Fadhila; Waluyadi Waluyadi; Zelfi Ghaffar Aufiya (Ann Publisher, 2026)
Background. This research is motivated by the increasing number of cases of sexual violence against children, which have serious impacts, both physically and psychologically. Empirical data show that most of these crimes occur against children under the age of 18, with contributing factors including weak social supervision, environmental influences, and abuse of close relationships by perpetrators. Aims. This study aims to examine the obstacles faced by investigators in handling cases of sexual violence against children within the jurisdiction of the Indramayu Police. Methods. The research method used was a qualitative normative approach. The legal materials used consisted of primary and secondary legal materials. The legal materials were collected through literature review and interviews, while data analysis was conducted prescriptively to provide solutions to the problems studied. Result. The results indicate that the perpetrators' modus operandi generally involves exploiting close relationships with the victims, such as family, friendships, or romantic relationships, accompanied by manipulation, persuasion, and abuse of trust. Conclusion. Obstacles faced by investigators include limited personnel, high caseloads, lack of information about the perpetrators, and difficulty obtaining statements from traumatized victims, resulting in suboptimal investigations.